The The Study of UX on Students’ Perception and Attitude of Using Zoom During Covid-19 Pandemic Using User Centered Design Method - Inacio Campos; Mira Kania Sabariah; Danang Junaedi (Journal of Computer System and Informatics (JoSYC), 2022)
The pandemic of COVID-19 resulted in the physical shutdown which has now transformed education into an exclusive "online learning" model. Zoom is being used to evaluate the perceived usability as the reference platform. The students find it less collaborative, less interactive, boring, and less collaborative. From this perspective, the Usability of the current online learning platforms is an important factor, particularly because no physical classes are present. The User-Centered Design (UCD) approach was chosen for this study and using the Usability Scale (SUS) method to evaluate the interface. The objective of this study is to analyze user experience, design solutions and evaluate user interfaces that can meet user needs. A pre-survey to evaluate the difficulties of the Zoom application based on user experience, and a post-survey to see if the upgraded design can help the students using the Zoom application for online learning. Then, use the System Usability Scale (SUS) questionnaire approach to measure the system's usability. After the UCD approach was completed, the researcher did a follow-up survey. The results showed that SUS ratings went up to 85.12. As a result, the previously low acceptability ranges have been raised to acceptable. Additionally, the grade scale has been reclassified B. The Zoom program now has more features and is easier to use, and fulfills the students' needs.